Analisis Perencanaan Pemasangan Recloser pada Penyulang untuk Meminamilisr Pemadaman - Wijaya Kusuma; Ahmad Hermawan; Aulia Nur Rahma; Muhammad Ilham Rifqi (Elposys: Jurnal Sistem Kelistrikan, 2021)
One of the feeders in PT. PLN (Persero) ULP is the Selecta Feeder. Based on data, the Selecta Feeder experienced 34 disturbances from January 2018 to November 2020, with a feeder load of 164 A, 106 distribution transformers (GTT), and a network length of 62.602 km. The Selecta Feeder is the feeder with the highest load in PT. PLN (Persero) ULP Batu, and the high number of disturbances on the Selecta Feeder will have a significant impact on the revenue of PT. PLN (Persero). There are 7 load break switches (LBS) and 1 recloser installed on the Selecta Feeder. During the period of January 2018 to November 2020, most of the disturbances occurred due to external factors and happened in sections 3 and 4. Therefore, it is necessary to ensure the continuity of electrical energy supply on the Selecta Feeder to anticipate widespread power outages by adding an installed recloser. A recloser is a protective device that can detect excessive current due to short circuits between phases or phase-to-ground faults, where the recloser automatically interrupts and recloses the circuit with an adjustable time delay.